1999
DOI: 10.1108/13620439910279752
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on customer satisfaction with employment services

Abstract: This study examined gender differences of the customer expectations and satisfaction of job seekers with employment and training services by a state government in the USA. A customer satisfaction survey was administered yielding 1,393 responses from individuals who applied for employment and training services from the New Jersey Employment Service. It was found that women generally have higher expectations regarding the importance of service delivery issues than their male counterparts. However, no differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…There is a stream of research that consistently finds variations in satisfaction ratings based on numerous customer characteristics (e.g., Bryant and Cha 1996;Mittal and Kamakura 2001;Peterson and Wilson 1992;Ross et al 1999;Varki and Rust 1997;Venn and Fone 2005). Recently, it has been found that customer characteristics moderate the relationship between satisfaction and behavioral outcomes (Baumann, Burton, and Elliott 2005;Mägi 2003;Mittal and Kamakura 2001;Homburg and Giering 2001;Homburg, Giering, and Menon 2003;Keiningham, Perkins-Munn, and Evans 2003).…”
Section: Moderators In the Satisfaction-share-of-wallet Relationshipmentioning
confidence: 93%
“…There is a stream of research that consistently finds variations in satisfaction ratings based on numerous customer characteristics (e.g., Bryant and Cha 1996;Mittal and Kamakura 2001;Peterson and Wilson 1992;Ross et al 1999;Varki and Rust 1997;Venn and Fone 2005). Recently, it has been found that customer characteristics moderate the relationship between satisfaction and behavioral outcomes (Baumann, Burton, and Elliott 2005;Mägi 2003;Mittal and Kamakura 2001;Homburg and Giering 2001;Homburg, Giering, and Menon 2003;Keiningham, Perkins-Munn, and Evans 2003).…”
Section: Moderators In the Satisfaction-share-of-wallet Relationshipmentioning
confidence: 93%
“…Hackett, Mirvis, and Sales () find that women have lowered expectations of new technologies in the workplace. Alternatively, Ross, Fleming, Fabes, and Frankl () find that women have consistently higher expectations of employment services on a variety of dimensions, including courteousness, helpfulness, and empathetic nature of the staff; accuracy of information available; and cleanliness of facility. While women have higher expectations, they do not translate into differences in satisfaction levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a stream of research that consistently finds variations in satisfaction ratings based on numerous customer characteristics (e.g., Bryant and Cha 1996; Mittal and Kamakura 2001; Peterson and Wilson 1992; Ross et al 1999; Varki and Rust 1997; Venn and Fone 2005). Recently, it has been found that customer characteristics moderate the relationship between satisfaction and behavioral outcomes (Baumann, Burton, and Elliott 2005; Mägi 2003; Mittal and Kamakura 2001; Homburg and Giering 2001; Homburg, Giering, and Menon 2003; Keiningham, Perkins-Munn, and Evans 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%